Raziskovalna dejavnost v zdravstveni negi na slovenskem - prispevek Stane Kavalič - Mihelič-Zajec, Andreja (Obzornik zdravstvene nege, 1999)
The introductory part points to the importance of familiarity with the past for successful planning of the development of nursing care. Nurses who carry out and shape this professional field often ask themselves questions about thevery beginnings. Literature survey present the research work of Stana Kavalič in nursing care. Conditions required for research are defined and the contribution of Stana Kavalič in the transfer of knowledge stressed, as well as her deep understanding of methodology and pratical research.
Keywords: Nursing research; raziskovalna dejavnost; Trends; zdravstvena nega